HYDROGEN – AN EFFECTIVE “TOOL” FOR ACHIEVEING A CARBON-NEUTRAL FUTURE: ACHIEVEMENTS, TRENDS, CHALLENGES - BOICHENKO, SERGII; HAVRYS, DMYTRO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The effective development of hydrogen technologies is an important aspect in the context of the global energy transition. Forecasts for the future of hydrogen as an energy source demonstrate its potential to become an important element in the fight against climate change, in particular due to its ability to be a clean, versatile and renewable energy source. However, achieving this goal requires addressing a number of technical, economic and infrastructural challenges. First and foremost, it is important to integrate hydrogen technologies into existing energy systems to ensure efficient production, storage and transportation of hydrogen. The development of this technology depends on many factors, including the availability of renewable energy sources, as well as the technical characteristics of the electrolysers and infrastructure. Currently, the greatest progress is being made in regions such as Europe, Asia, North America and Australia, where hydrogen production and use projects are being actively implemented. Particular attention is drawn to initiatives that promote the development of hydrogen infrastructure in Ukraine, where hydrogen can become an important element for the transition to a more sustainable energy model. This publication contains a technical overview of electrolysers, a classic review of the produced review, and international initiatives and projects that contribute to the development of hydrogen technologies and its integration into energy networks. Analysis of the international dynamics of hydrogen energy development confirms its priority tendency and demonstrates its strategic importance in achieving the goals of decarbonization, energy security and sustainable development. Ukraine, given its natural resources, infrastructure and strategic location, has every chance of becoming one of the key players in the European hydrogen market. This investigation is an important scientific and practical result that will allow not only to form a comprehensive picture of current achievements, but also to identify the main barriers to a sustainable hydrogen future and to form an understanding of the prospects for the implementation of hydrogen technologies.